On the Preventative Effect of Sanctions for Drug Crime: The United States, Germany, and Portugal (Archives of Criminology, 2023)
One of the most discussed types of crime in Western countries is the use and sale of illegal drugs, especially hard drugs. The debate has become more heated over the few last years in the context of controversies over migration from the south to the north and an intensification of drug dealing. On the one hand, we find an increasing acceptance of soft drugs, while on the other hand, conservative groups argue for harsher punishment to reduce the problem. This chapter discusses the developments in the USA, Germany, and Portugal and raises doubts about the effectiveness of more and harsher punishment on crime prevention.